ROTOR MECHANICAL STRESS ANALYSIS OF A DOUBLE-SIDED AXIAL FLUX PERMANENT MAGNET MACHINE - Pranjić, Franjo; Virtič, Peter (Journal of Energy Technology, 2024)
This paper presents the mechanical stress analysis (MSA) of a rotor disk in a double-sided axial flux permanent magnet machine (AFPMM). The analysis considers the rotor of a prototype AFPMM with a double external rotor and single internal stator. Rotor disks of the prototype AFPMM are construct- ed of two 11.6 mm-thick steel disks and represent around 50% of the total weight of the machine. The new rotor disk thickness was determined based on a rotor axial displacement due to the attractive force between the permanent magnets on opposite rotor disks.